Studies on trypanosoma rangeli tejera, 1920 x-its comparison with trypanosoma cruzi chagas, 1909. Infection in differents st ages of rhodnius prolixus stal, 1859 - N. Añez; M. Molero; A. Valderrama; Elsa Nieves; D. Cazorla; M. Castro; V. Márquez (Universidad del Zulia,Facultad de Medicina,Departamento de Enfermedades Infecciosas y Tropicales, 1992)
The comparison among specimens of Rhodnius prolixus, at different stages of development, exposed to infections by Trypanosoma rangeli and Trypanosoma cruzi, revealed that the bugs exposed to T. cruzi showed a significant higher susceptibility to infection than that observed in the groups exposed to T. rangeli or to the mixture of both parasites. The similar mortality rate recorded in uninfected and T. cruzi infected bugs confirms that this parasite is harmless to R. prolixus. On the other hand. T. rangeli produces its pathological effect although the bugs ingest a relatively low number of flagellates. suggesting the existen ce of a direct relation between the amount of ingested parasites and the mortality produced. In mixed infection, T. cruzi does not inhibit the harmful effect ofT. rangeli on R. prolixus. The life cyc1e of R. prolixus is not affected by high infection of T. cruzi or low infection by T. range~. However, when bugs ingested a high amount of flagellates ofT. rangeli in mixed infections, the time to reach the adult stage in relation to controls, was significantIy longer. The epidemiological significance of the present results is discussed.